Microbiological and Physicochemical Quality of Dairy Goat Milk in a Tropical Smallholder System: A Case Study of Padayo Goat Farm - Hilda Susanty; Eli Ratni; Anisaul Fitri Wahyuni; Shahid Ullah Khan (Andalasian Livestock, 2026)
Goat milk is increasingly recognized as a functional food in developing countries because of its high nutritional value and digestibility. However, maintaining its microbiological safety and physicochemical stability remains challenging, particularly in smallholder systems under tropical conditions. This study evaluated the quality of dairy goat milk based on total plate count (TPC), pH, and alcohol stability at a smallholder farm in West Sumatra, Indonesia. Milk samples were collected from 16 lactating goats and analyzed using standard laboratory methods. The average TPC was 3.58 × 10⁴ CFU/mL, well below the maximum permissible limit of 1 × 10⁶ CFU/mL Indonesian and Thai Agricultural Standards. The mean pH value was 6.71 ± 0.01, indicating fresh milk conditions, while all samples exhibited negative alcohol test results, confirming protein stability and the absence of early spoilage. These findings demonstrate that high-quality milk can be produced in tropical smallholder systems when basic hygiene practices are properly implemented. This study provides empirical evidence supporting the role of smallholder dairy goat farms in ensuring food safety and sustainable dairy development in emerging economies.